2020
DOI: 10.1074/jbc.ra119.010768
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the N-terminal domain of the trypanosome flagellar protein BILBO1 reveals a ubiquitin fold with a long structured loop for protein binding

Abstract: Trypanosoma brucei is a protist parasite causing sleeping sickness and nagana in sub-Saharan Africa. T. brucei has a single flagellum whose base contains a bulblike invagination of the plasma membrane called the flagellar pocket (FP). Around the neck of the FP on its cytoplasmic face is a structure called the flagellar pocket collar (FPC), which is essential for FP biogenesis. BILBO1 was the first characterized component of the FPC in trypanosomes. BILBO1's N-terminal domain (NTD) plays an essential role in T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…We have previously identified several key aromatic residues in BILBO1-NTD that are important for the BILBO1 function and involved in the FPC4-BILBO1 interaction (residues Y89, F89, W71, Y64) [14,15]. The crystal structure of the BILBO2-FPC4 protein complex also suggests that residues F63, F88, and W70 in the BILBO2-NTD are involved in the interaction with FPC4.…”
Section: Mutation Of Critical Interface Residues Abolishes the Bilbo2mentioning
confidence: 98%
See 3 more Smart Citations
“…We have previously identified several key aromatic residues in BILBO1-NTD that are important for the BILBO1 function and involved in the FPC4-BILBO1 interaction (residues Y89, F89, W71, Y64) [14,15]. The crystal structure of the BILBO2-FPC4 protein complex also suggests that residues F63, F88, and W70 in the BILBO2-NTD are involved in the interaction with FPC4.…”
Section: Mutation Of Critical Interface Residues Abolishes the Bilbo2mentioning
confidence: 98%
“…This supports the hypothesis that the NTDs share a similar function as they can compensate for each other in both chimera. This is imperative because we have demonstrated that minor changes in BILBO1-NTD, such as the W71A mutant, were lethal [14].…”
Section: The N-terminal Domain Of Bilbo2 Is Homologous To the Bilbo1 mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the identity and similarity reach 32% and 38% respectively between their NTD (Fig 5A). Importantly, the two residues (Y64, W71), which were previously shown to play a critical role in BILBO1's interaction with FPC4 and cell viability [9,[13][14][15], are conserved or identical in BILBO2 (i.e. F63, W70).…”
Section: The N-terminal Domain Of Bilbo2 Is Homologous To the Bilbo1 Nterminal Domainmentioning
confidence: 99%